Decreasing the effectiveness for shooting the basket: A basic problem for the U16, U18, and U20 European women`s basketball - Borukova, M. A. (SportMont, 2020)
The view of experts regarding women basketball in Europe is that in recent years the effectiveness of shooting baskets is slowly diminishing, which impacts the game negatively. The purpose of our research is to effect studies related to the effectiveness of shooting the basket in women basketball for various age groups: U16, U18, and U20. For the research, we have studied specialized literature and analysed game effectiveness statistic data from the Genius Sport official system for registering the game indicators of the European Basketball Federation (FIBA). The initial data are processed mathematically-statistically by variation analysis, relative share for establishing the effectiveness of shooting baskets from various distances, and comparative analysis. We have researched shooting effectiveness data from the last European championships for the three age groups. The results show a decrease in the competitors` skills for effecting baskets by the growth of age. We can conclude that women`s basketball is a dynamic sport with many elements, but the effectiveness of shooting baskets is at its core, which is something that is often forgotten. Coaches working at each level should use at least 30% of the training and training process for specific shooting exercises for the basket; this is the minimum that can stop this process so that the game of basketball does not go into an existential crisis.